Separate and Unequal – Title I and Teacher Quality - Rivera Rodas, Elizabeth Iris (Education Policy Analysis Archives, 2019)
Research has shown that Title I’s “comparability” provision causes gaps in noncategorical per pupil teacher funding. Using a unique dataset that merges 2009-2010 New York City (NYC) Department of Education value-added scores, school finance data, and school demographic data, this study not only confirms that NYC Title I elementary schools received less noncategorical per pupil teacher funding than non-Title I elementary schools, but these schools also had lower quality teachers. This paper provides the first evidence of a negative relationship between noncategorical per pupil teacher funding and the percentage of below average teachers even when controlling for certain school demographics. If Title I elementary public schools in New York City have lower quality teachers, then the students that are served by these schools are not receiving the same quality of education as their peers. Changing the comparability provision in Title I funding would result in more equitable funding.